Biology and Control of Japanese Climbing Fern (Lygodium japonicum) - Patrick J. Minogue; Stella Jones; Kimberly K. Bohn; Rick L. Williams (EDIS)
FOR-218, a 7-page illustrated fact sheet by Patrick J. Minogue, Stella Jones, Kimberly K. Bohn, and Rick L. Williams, describes this non-native, invasive vine which is widespread in damp areas in north and West Florida — its biology and control measures. Includes references. Published by the UF School of Forest Resources and Conservation, May 2009.